Ontological multivocity in Aristotle's Metaphysics - Buongiorno, A (2023)
This thesis examines Aristotle’s claim that being is said in many ways, which I refer to as ‘Ontological Multivocity’ or ‘OM’. It focuses on four occurrences of this claim, to be found in Metaphysics Γ2, Δ7, Z1, and Z4. Across these chapters, Aristotle endorses two different versions of OM, which I will call ‘Focal OM’ and ‘Global OM’. My overall aim is to determine how these two versions of OM should be understood and how they relate to one another. Since Focal OM receives the lion’s share of Aristotle’s attention, my central aim is to offer a textually supported and theoretically plausible interpretation of this particular version of OM. Roughly put, Focal OM states that substances are called ‘beings’ primarily whereas non-substances are so called derivatively. This view is first introduced in Γ2 and then progressively refined over the course of Δ7, Z1, and Z4. In Γ2, Focal OM may be interpreted in either of two ways, namely as a claim about existence or about predication. In Δ7, it is presented as a claim about predication: substances are per se, genuine, or primary, whereas non-substances are per accidens, non-genuine, or derivative subjects of any old type of predication. In Z1, it is presented as a claim about a certain type of predication: substances are per se, genuine, or primary, whereas non-substances are per accidens, non-genuine, or derivative subjects of essential predication. In Z4, it is presented as an even more definite claim about predication: as long as they meet certain baseline requirements for unity, essential predications qualify as definitions; subject to this proviso, substances are per se, genuine, or primary, whereas non-substances are per accidens, non-genuine, or derivative objects of definition. Aristotle’s argument for this view in Z4 displays certain shortcomings: however, these can be overcome by employing predicational principles which are clearly available to him in this chapter; subject to these adjustments, Focal OM makes for a plausible theory of definitional priority, which Aristotle explicitly expounds in the adjacent Z5.